2015
DOI: 10.1080/13552074.2015.1096040
|View full text |Cite
|
Sign up to set email alerts
|

Women rebuilding lives post-disaster: innovative community practices for building resilience and promoting sustainable development

Abstract: H. (2015) 'Women rebuilding lives post-disaster : innovative community practices for building resilience and promoting sustainable development.', Gender and development., 23 (3). pp. 433-448.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
92
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 111 publications
(104 citation statements)
references
References 6 publications
(1 reference statement)
1
92
0
1
Order By: Relevance
“…Nor should it be assumed that women would participate in the same way as men, as is demonstrated by a recent case study of the Alianzia de Mujeres Activas (AMA; Alliance of Active Women) [19]. The AMA organized following the devastating impacts of multiple hurricanes in Volusia County, Florida in 2004-2005.…”
Section: "Active" Participation and Representationmentioning
confidence: 99%
See 4 more Smart Citations
“…Nor should it be assumed that women would participate in the same way as men, as is demonstrated by a recent case study of the Alianzia de Mujeres Activas (AMA; Alliance of Active Women) [19]. The AMA organized following the devastating impacts of multiple hurricanes in Volusia County, Florida in 2004-2005.…”
Section: "Active" Participation and Representationmentioning
confidence: 99%
“…Drolet et al [19] reported women's workload effectively doubled following 2010-2011 floods in Pakistan, as women took on roles in reconstruction and agriculture considered "men's work" in addition to their traditional roles as carers, whereas men's workload remained unchanged. Men suffered employment loss and damaged livelihoods.…”
Section: Women's Employmentmentioning
confidence: 99%
See 3 more Smart Citations